INFLUÊNCIA DA PECUÁRIA E SUA IMPLICAÇÃO NA SUSTENTABILIDADE DA MATA CILIAR DO RIO ZUTIUA,MARANHÃO,BRASIL. - LAGO, Caruline Silva (2012)
Riparian forests are extremely important in the conservation and maintenance of ecosystem services, economic and social, having a key role in the sustainability of a region. Based on this, This study aimed to analyze the structure of riparian vegetation of the river Zutiua regarding the influence of livestock areas targeting the sustainable planning of riparian vegetation in the region of sub-basin Zutiua, Maranhão. We allocated 10 plots of 10x50m (500 m²) perpendicular to the river's course at different distances from the area of use (grazing). In the sampling, all individuals with a minimum of 5 cm diameter at 1.30 m at breast height were recorded and the total height of trees. Were sampled the 538 trees, 42 species, 34 families, resulting in a density of 978.18 plants / ha. The height and diameter were respectively 5.11 m and 13.58 cm. The Shannon diversity index (H ') was 2.452 for species and families was 2.083 and the index of equability (J') of 0.65. The richest families were Arecaceae, Myrtaceae, Leguminosae, Polygonaceae and Lecythidaceae. The species that had the highest IVI values were Symmeria paniculata Benth., Orbignya phalerata Mart., Bactris brongniartii Mart., Sp 2, sp.4, Pithecolobium sp. Crataeva tapia L. Sp.12 and Cecropia glaziovi Snethlage. The results show that the remaining areas are characterized by the presence of secondary species and the large number of young individuals. In linear regression analysis performed to test the effect of different distances from the use area in the values of height, diameter, number of individuals and number of species, did not achieve significant value, in other words, the values found for these parameters were not associated with the distance from the area of use. In the buffer analysis, the generated map showed that the cattle have not affected the riparian forest, which was not observed "in situ", where vast areas have no riparian vegetation in the river Zutiua, due to the presence of livestock. This probably is due to the continued use of forest resources by local residents, who use and end up doing some species, thus a form of selective logging by changing the vegetation structure. However, it is apparent that the main cause of habitat loss and degradation of riparian vegetation in the region is the extensive breeding of cattle.